1993
DOI: 10.2165/00003088-199325060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interactions with Antimicrobial Agents

Abstract: As new classes of antimicrobial drugs have become available, and new uses found for older drugs, pharmacokinetic drug interactions with antimicrobials have become more common. Macrolides, fluoroquinolones, rifamycins, azoles and other agents can interact adversely with commonly used drugs, usually by altering their hepatic metabolism. The mechanisms by which antimicrobial agents alter the biotransformation of other drugs is increasingly understood to reflect inhibition or induction of specific cytochrome P450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 231 publications
1
60
0
1
Order By: Relevance
“…Since the pharmacokinetics of ddI in dogs are similar to those from limited observations in humans, similarities in metabolic profiles of these two species (i.e., xanthine oxidase) may explain the lack of interaction found in this trial (see below). Like other azoles, fluconazole is an inhibitor of multiple hepatic P-450 enzymes; it also appears to inhibit some non-P-450 enzymes, such as uridine diphosphate-glucurosyl transferase, which is responsible for the metabolism of ZDV (6,9,19). However, we found that the pharmacokinetics of ddI are not altered by fluconazole when both are given at commonly prescribed dosages.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Since the pharmacokinetics of ddI in dogs are similar to those from limited observations in humans, similarities in metabolic profiles of these two species (i.e., xanthine oxidase) may explain the lack of interaction found in this trial (see below). Like other azoles, fluconazole is an inhibitor of multiple hepatic P-450 enzymes; it also appears to inhibit some non-P-450 enzymes, such as uridine diphosphate-glucurosyl transferase, which is responsible for the metabolism of ZDV (6,9,19). However, we found that the pharmacokinetics of ddI are not altered by fluconazole when both are given at commonly prescribed dosages.…”
Section: Discussionmentioning
confidence: 57%
“…Fluconazole is well absorbed in the HIV population and is frequently prescribed for prophylaxis and treatment of fungal infections (6). However, fluconazole inhibits a number of hepatic P-450 enzymes that are responsible for the metabolism of many drugs, such as theophylline, phenytoin, cyclosporin, and rifabutin (9,16,21). In addition, fluconazole has recently been shown to decrease clearance of zidovudine (ZDV), a drug which is metabolized primarily by glucuronidation (19).…”
mentioning
confidence: 99%
“…In addition, RIF-mediated induction of CYP3A enzyme activity occurred in a concentration-dependent fashion up to 30 µM, but at a higher concentration (100 µM), the increased activity was reduced. These phenomena can be attributed to the biochemical properties of RIF; it has the ability not only to induce CYP3A subfamily enzymes 35) but also to inhibit the activities of several CYP enzymes, including CYP3A4. 36) CALUX in HPL-A3 was further increased not only by hPXR-selective activators (RIF and CLO) but also by human/ mouse/rat PXR activators (TAM and NIC), while no such significant increases by mouse/rat PXR activators (DEX and PCN) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, CYP3A4 inducers such as rifampicin and rifabutin can reduce plasma concentrations of certain drugs up to 40-fold, effectively abolishing their efficacy (Gillum et al, 1993;Grange et al, 1994). For example, enhanced metabolism, produced by rifampicin, of the CYP3A substrate cyclosporine has resulted in organ graft rejections (Lucey et al, 1990).…”
Section: Introductionmentioning
confidence: 99%